Pengaruh Waktu Antrian Check-In Counter terhadap Kepuasan Penumpang Maskapai Citilink di Bandar Udara Jenderal Ahmad Yani Semarang - Yohana Arifa; Amelia Puspa Tamara (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
Based on PM 30 of 2021 concerning User Service Standards, check-in services at the airport are carried out at least 2 hours before the departure schedule, while the check-in service procedure has a time limit of two minutes and thirty seconds for each passenger, and the check-in queue can last for twenty minutes per passenger. This study aims to determine whether there is an effect of check-in counter queue time on Citilink airline passenger satisfaction at General Ahmad Yani Airport, Semarang and how big the influence is. This study uses a quantitative approach. This research was conducted at General Ahmad Yani Airport, Semarang with a focus on the object of the Citilink airline passenger check-in counter queue. The research period was from August to February 2024. The questionnaire was used as a data collection tool in the form of a form containing questions or statements that must be filled in for 100 respondents. Based on the results of the test and data analysis that has been done, the effect of check-in counter queue time on Citilink airline passenger satisfaction at General Ahmad Yani Airport Semarang, the results of the hypothesis test obtained t count greater than t table, namely 5.745> 1.660 and with a significant value smaller than the probability of 0.000 <0.05, it can be concluded that Ha is accepted and Ho is rejected or can be called the queue time variable has a positive effect on the passenger satisfaction variable. This means that if the queue time at the check-in counter experienced by passengers is getting longer because the service provided is still not in accordance with the standard, then passenger satisfaction will have an effect resulting in higher passengers who are less satisfied and vice versa if the queue time is short or in accordance with the provisions, passengers will feel satisfied.